Improvement on Structural Forms of Pile Group Foundations of Deepwater Bridges. (14th August 2019) - Yu, Enbo; Ren, Sen; Tang, Haojun; Li, Yongle; Fang, Chen
Abstract : As long-span cross-sea bridges extend to deeper sea areas, the bridge pile tends to increase in its slenderness ratio and becomes more susceptible to waves. To improve the structural stability at the construction stage, this study analyses wave-induced response of foundations. The wave theory and the method used for computing wave forces on foundations are first introduced. Then, a pile group foundation is taken as the research object, and different pile lengths ranging from 16 m to 46 m are considered. The wave-induced response of the piles and the cap is calculated. After understanding the effect of the pile length, three optimized foundations are proposed with the aim of reducing the free length of the pile, and the corresponding finite element models are established to compare their wave-induced response. The results show that the displacement at the top of the foundation increases with the increase in the pile length until the cap partly emerges from water and so does the internal force at the bottom. Setting a constraint in the middle of the piles can reduce their free lengths and is favourable to the wave-induced response of the foundation except for the shearing force. A stronger constraint shows better effects on improvement of the stability of the foundation. The conclusions provide reference for optimization on pile foundations of deepwater bridges.